Solar elastosis: Case report and review - Tanya Khaitan; Ramaswamy Pachigola; Arpita Kabiraj; Uday Ginjupally (Wolters Kluwer Medknow Publications, 2016)
Solar elastosis is degenerative dermal disease of the photodamaged skin, associated with aging and influenced by hereditary factors such as pigmentation, exposure to sunlight and wind. The disease is characterized by the accumulation of abnormal elastic tissue in the dermis. Solar elastotic syndromes include solar elastosis, Favre-Racouchot syndrome, elastotic nodules of the ears, collagenous and elastotic plaques of the hands, and colloid milia. The most common solar elastotic syndrome is solar elastosis. The chief etiological factors contributing to the lesion include chronic exposure to sunlight (ultraviolet, visible, and infrared radiation). Ultraviolet-A radiation causes erythema and its deep penetration into the dermis causes inexplicably chronic photodamage. Here, we present a case report of 32-year-old female with a distinctive clinical presentation.